Muḥammad Nāṣīr al-Dīn al-Albānī and traditional Hadith criticism - Melchert, C (Edinburgh University Press, 2016)
Muḥammad Nāṣir al-Dīn al-Albānī (d. 1999) was an influential Syrian hadith critic. A major advocate of Salafism, he proposed to infer rules directly from hadith, bypassing the historic Sunni schools of law. He taught in Saudi Arabia 1961-3 but had to leave because of aberrant legal opinions; for example, that it was unnecessary to fast in Ramadan if one could not see daylight, as in a house with the windows blocked, that it was unnecessary to remove one’s footwear to pray, and that the full-face veil was unnecessary. His method of hadith criticism seems to rely heavily on evaluations of men by the most prominent medieval critics, a simplistic interpretation of the medieval literature. He is to be admired for accepting the consequences of his programme, though, daring to identify weak hadith in the most respected medieval collections, sternly dismissing rules based only on custom or doubtful hadith reports. Willy nilly, he seems to have provoked a re-examination of medieval methods of hadith criticism among Muslim scholars uninfluenced by recent scholarship in the same direction by Eerik Dickinson and others.